Particle beams from laser-irradiated solids at ultrahigh intensities - Nerush, E.N.; Kostyukov, I.Yu. (Вопросы атомной науки и техники, 2013)
Laser-solid interactions at the intensity range 10²³…10²⁶ W cm⁻² and the plasma density about 10²⁴ cm⁻³ are studied by means of numerical simulations. This range of parameters is extremely important for various laser applications such as fast ignition, gamma-ray generation and ion acceleration, and will be reached by the next generation of intense laser facilities. An overview of the interaction regimes is given.